Scale and density invariant head detection deep model for crowd counting in pedestrian crowds - Khan, Sultan Daud; Basalamah, Saleh (The Visual computer, 2021)
Crowd counting in high density crowds has significant importance in crowd safety and crowd management. Existing state-of-the-art methods employ regression models to count the number of people in an image. However, regression models are blind and cannot localize the individuals in the scene. On the other hand, detection-based crowd counting in high density crowds is a challenging problem due to significant variations in scales, poses and appearances. The variations in poses and appearances can be handled through large capacity convolutional neural networks. However, the problem of scale lies in the heart of every detector and needs to be addressed for effective crowd counting. In this paper, we propose a end-to-end scale invariant head detection framework that can handle broad range of scales. We demonstrate that scale variations can be handled by modeling a set of specialized scale-specific convolutional neural networks with different receptive fields. These scale-specific detectors are combined into a single backbone network, where parameters of the network is optimized in end-to-end fashion. We evaluated our framework on challenging benchmark datasets, i.e., UCF-QNRF, UCSD. From experiment results, we demonstrate that proposed framework beats existing methods by a great margin.